2023
DOI: 10.1212/wnl.0000000000206831
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Migraine, Migraine Phenotype, and Risk of Adverse Pregnancy Outcomes

Abstract: Background and Objective:Migraine is a highly prevalent neurovascular disorder among reproductive-aged women. Whether migraine history and migraine phenotype might serve as clinically useful markers of obstetric risk is not clear. The primary objective of this study was to examine associations of pre-pregnancy migraine and migraine phenotype with risks of adverse pregnancy outcomes.Methods:We estimated associations of self-reported physician-diagnosed migraine and migraine phenotype with adverse pregnancy outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
5
0
1
Order By: Relevance
“…Chen et al, in a three-year nationwide population-based database study in Taiwan, found that pregnant women who had migraines had a 1.34 times higher risk of preeclampsia than pregnant women who did not have migraine (8). As mentioned earlier, migraine is associated with an elevated risk of hypertensive disorders of pregnancy (6,7,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Chen et al, in a three-year nationwide population-based database study in Taiwan, found that pregnant women who had migraines had a 1.34 times higher risk of preeclampsia than pregnant women who did not have migraine (8). As mentioned earlier, migraine is associated with an elevated risk of hypertensive disorders of pregnancy (6,7,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 93%
“…Previously, Facchinetti et al (17), in a study involving a large prospective cohort of 702 Italian women with singleton pregnancies, reported that migraine was associated with preeclampsia. In another large cohort study (19,694 participants), women who had pre-pregnancy migraine were found to have a 60.0% higher risk of preeclampsia (relative risk ¼ 1.40) than those who did not have pre-pregnancy migraine (6). A recent systematic review that included 14 studies revealed that pregnant women who had migraines had a 2.07 times higher risk of having preeclampsia than pregnant women who did not have migraine (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited knowledge pertaining to migraine and pregnancy outcomes makes it difficult to counsel patients or improve the management of pregnant women with migraine. In this issue of Neurology ®, Purdue-Smithe et al 6 publish a study that evaluates the association of prepregnancy migraine and migraine phenotype (i.e., with or without aura) and the risks of adverse pregnancy outcomes, including gestational diabetes mellitus, preeclampsia, gestational hypertension, preterm delivery, and low birthweight in a prospective cohort of nurses in the United States. The authors used data from the Nurses' Health Study II, which started surveys in 1989 and followed with biennial questionnaires.…”
mentioning
confidence: 99%